A Cognitive Prototype Model of Moral Judgment and Disagreement. Issue 1 (2nd January 2017) - Larson, Carol A.
Abstract : Debates about moral judgments have raised questions about the roles of reasoning, culture, and conflict. In response, the cognitive prototype model explains that over time, through training, and as a result of cognitive development, people construct notions of blameworthy and praiseworthy behavior by abstracting out salient properties that lead to an ideal representation of each. These properties are the primary features of moral prototypes and include social context interpretation, intentionality, consent, and outcomes. According to this model, when the properties are uniform and coherent, they depict a promoral or immoral prototype, relative to the orientations of the properties. A promoral prototype is represented by an action that is supported by the culture, intentionally benevolent or other-regarding, consensual, and resulting in positive outcomes. An immoral prototype is an action that is condemned by the culture, intentionally malevolent or self-serving, lacking consent, and resulting in negative outcomes. It is hypothesized that moral prototypes will result in a high level of agreement and require effortless processing. Alternatively, when properties conflict or the situation deviates from the prototype, a nonprototype will result. It is hypothesized that nonprototypical situations will act as a source of moral disagreement and may require more effortful processing.